THE IMPLEMENTATION OF ISLAMIC ECONOMIC LAW IN INDONESIA’S MARITIME BORDER REGION: A CASE STUDY OF THE RIAU ISLANDS - M Taufiq; Ali Ridho; Kudrat Abdillah; Jamaluddin Shiddiq (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines how Islamic economic law is implemented in Indonesia’s maritime border region, focusing on the Riau Islands, and explains why its application in this socially plural, geographically fragmented, and transnational setting differs from more institutionally developed regions. This research employed a qualitative explanatory case study in three areas of the Riau Islands Province: Batam City, Tanjungpinang City, and Lingga Regency. Primary data was collected through participatory observation and in-depth interviews with 14 informants, including government officials, religious leaders from Islamic organizations, practitioners of Islamic economics, and operators of halal SMEs; secondary data was obtained from an analysis of dozens of reputable academic articles and relevant books. The data were analyzed thematically using the Miles and Huberman interactive model and validated through triangulation and member checking. The study finds that Islamic economic law is practiced primarily as a lived ethical system rather than as a fully formalized legal framework. In many local transactions, values such as honesty, fairness, trust, and the avoidance of riba are strongly maintained, yet formal sharia contracts, regulatory support, and institutional access remain uneven, especially in island and peripheral areas. Its implementation is shaped by low Islamic financial literacy, limited institutional infrastructure, dispersed geography, and continuous negotiation between sharia principles, market efficiency, and interfaith social relations. The findings are limited to a qualitative case study in three locations and therefore are not statistically generalizable to all maritime border regions. However, they highlight the need for context-sensitive policies, literacy strengthening, and community-based Islamic economic development. This study contributes to Islamic economic law scholarship by bringing border-region evidence into a field largely dominated by urban and institutional studies, showing that implementation depends not only on legal formalization but also on local culture, social networks, and transnational realities.